Association of single nucleotide polymorphism in patatin like phopholipase domain containing 3 (PNPLA3) gene with paediatric non-alcoholic fatty liver disease - Rubaiyat Alam; Kaniz Fathema; Md Rukunuzzaman; Khan Lamia Nahid; Sharmin Mahbuba; Lubana Akram; Abu Naser Ibne Sattar (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is the most unabating cause of chronic liver disease in children and adolescents. This study aimed to examine the association of single nucleotide polymorphism in patatin-like phospholipase domain containing 3 (PNPLA3) gene with paediatric non-alcoholic fatty liver disease.